Structure and functioning of wild and agricultural grazing ecosystems: A comparative review - Kleppel, Gary S.; Frank, Douglas A. (Frontiers in Sustainable Food Systems, 2022)
For more than 10 million years, large, herd forming ruminants have thrived as parts of sustainable grazing ecosystems. Conversely, since their domestication 8,000–11,000 years ago, cattle, sheep, and goats have often exhibited dysfunctional relationships with the ecosystems they inhabit. A considerable literature, developed over decades, documents the negative impacts of animal agriculture and associated activities (e.g., feed production) on grassland ecosystems. Coincident with the accumulating data documenting the impacts of “conventional” animal agriculture, has been a growing interest in restoring functionality to agricultural grazing ecosystems. These “regenerative” protocols often seek to mimic the structure and functions of wild grazing ecosystems. The objectives of this paper were two-fold: First to review the literature describing the structure and some key functional attributes of wild and agricultural grazing ecosystems; and second, to examine these attributes in conventionally and regeneratively managed grazing ecosystems and, assuming the wild condition to be the standard for sustainable grazer-environment relationships, to ascertain whether similar relationships exist in conventionally or regeneratively managed agricultural grazing ecosystems. Not unexpectedly our review revealed the complexity of both wild and agricultural grazing ecosystems and the interconnectedness of biological, chemical, and physical factors and processes within these systems. Grazers may increase or decrease system functionality, depending upon environmental conditions (e.g., moisture levels). Our review revealed that biodiversity, nitrogen cycling, and carbon storage in regenerative grazing systems more closely resemble wild grazing ecosystems than do conventional grazing systems. We also found multiple points of disagreement in the literature, particularly with respect to aboveground primary production (ANPP). Finally, we acknowledge that, while much has been accomplished in understanding grazing ecosystems, much remains to be done. In particular, some of the variability in the results of studies, especially of meta-analyses, might be reduced if datasets included greater detail on grazing protocols, and a common definition of the term, “grazing intensity.”